La crítica a la Filosofía de Ibn Jaldún y la purificación del Islam - González, Ángel Poncela (2016)
Abstract: This essay is framed in the eld of Islamic philosophy of the classical period. The Ibn Khaldun’ Introduction (al-muqadima) to the Universal History, provides an explanation of the state where the Philosophy in the lands of Islam was the fourteenth century, and the factors of its demise. The main cause of its decline was the intellectual traditionalists offensive deployed against philosophy. The philosophical theories (con dence in the power of reason and ability to know the causes and essences, establish articles of faith, purify the soul and fundation the happiness in knowledge and moral autonomy (Al-Muqqadima, I 30, p. 1042) offered a worldview that held an alternative life to Muslim life that would endanger the stability of the Islamic community. The Tunisian historian was designed to contain this threat by proposing a return to the traditional understanding of Islam that favors intuitive knowledge, interpretation of dreams and Su sm as the most pious way to live Islam. Key words: Intuitive knowledge; interpretation of dreams; Reason vs. Fatih. Medieval Authors: Ibn Khaldun. Resumen: El presente ensayo se enmarca en el ámbito de la Filosofía islámica del periodo clásico. La Introducción (al-muqadima) a la Historia Universal de Ibn Jaldún nos proporciona una explicación del estado en el que se encontraba la Filosofía en las tierras del Islam del siglo XIV, y de los factores de su desaparición. La causa principal de su declive fue la ofensiva que los intelectuales tradicionalistas desplegaron en contra de la Filosofía. Las teorías losó cas (con anza en el poder de la razón con capacidad para conocer las causas y las esencias, establecer los artículos de la fe, puri car el alma y establecer una felicidad fundada en el conocimiento y en la autonomía moral, Al-Muqqadima, I, 30, p. 1042) ofrecían una cosmovisión que encerraba una forma de vida alternativa a la vida musulmana que hacía peligrar la estabilidad de la comunidad islámica. El historiador tunecino intentó contener esta situación, proponiendo el regreso a la concepción tradicional del Islam al tiempo que privilegió el conocimiento intuitivo, la interpretación de los sueños y el Su smo como la forma más genuina y piadosa de vivir el Islam. Palabras clave: Conocimiento intuitivo; interpretación de los sueños; Razón vs. Fe. Autores medievales: Ibn Jaldún.